Heart rate deceleration and acceleration capacities associated with circadian rhythm of blood pressure in essential hypertension - Jijing Wang; Jinyi Xu; Lihong Yang; You Zhang; Rui Wu; Wentao Wang; Chuanyu Gao (BMC Cardiovascular Disorders, 2024)
Abstract Background This study aimed to investigate the potential association between the circadian rhythm of blood pressure and deceleration capacity (DC)/acceleration capacity (AC) in patients with essential hypertension. Methods This study included 318 patients with essential hypertension, whether or not they were being treated with anti-hypertensive drugs, who underwent 24-hour ambulatory blood pressure monitoring (ABPM). Patients were categorized into three groups based on the percentage of nocturnal systolic blood pressure (SBP) dipping: the dipper, non-dipper and reverse dipper groups. Baseline demographic characteristics, ambulatory blood pressure monitoring parameters, Holter recordings (including DC and AC), and echocardiographic parameters were collected. Results In this study, the lowest DC values were observed in the reverse dipper group, followed by the non-dipper and dipper groups (6.46 ± 2.06 vs. 6.65 ± 1.95 vs. 8.07 ± 1.79 ms, P < .001). Additionally, the AC gradually decreased (-6.32 ± 2.02 vs. -6.55 ± 1.95 vs. -7.80 ± 1.73 ms, P < .001). There was a significant association between DC (r = .307, P < .001), AC (r=-.303, P < .001) and nocturnal SBP decline. Furthermore, DC (β = 0.785, P = .001) was positively associated with nocturnal SBP decline, whereas AC was negatively associated with nocturnal SBP (β = -0.753, P = .002). By multivariate logistic regression analysis, deceleration capacity [OR (95% CI): 0.705 (0.594–0.836), p < .001], and acceleration capacity [OR (95% CI): 1.357 (1.141–1.614), p = .001] were identified as independent risk factors for blood pressure nondipper status. The analysis of ROC curves revealed that the area under the curve for DC/AC in predicting the circadian rhythm of blood pressure was 0.711/0.697, with a sensitivity of 73.4%/65.1% and specificity of 66.7%/71.2%. Conclusions Abnormal DC and AC density were correlated with a blunted decline in nighttime SBP, suggesting a potential association between the circadian rhythm of blood pressure in essential hypertension patients and autonomic nervous dysfunction.